La praxis teatral como herramienta política para la lucha subalterna. Un enfoque antropológico - Alvarado Castro, Iván; Alvarez Barragan, Gorka (Nómadas. Critical Journal of Social and Juridical Science, 2016)
“Art for art´s sake” could be seen as one of the slogans for political artist deactivation. Political theater, struggling against the possibility of being absorbed by the market, tries to find its way of escape, its little hole from where taking breath. This article shows theater as a subaltern tool for fighting and mantains that theater trainining and playing, extended to anyone and linked to a concrete philosophical view, becomes to an ontological agent of change of political subjects.